2009
DOI: 10.1063/1.3187732
|View full text |Cite
|
Sign up to set email alerts
|

A study on stability and thermophysical properties (density and viscosity) of Al2O3 in water nanofluid

Abstract: The dispersion and stability of nanofluids obtained by dispersing Al2O3 nanoparticles (obtained from different sources) in water have been analyzed. The differences arising from different dispersion techniques, the resulting particle size distribution, and time stability among the different samples are evaluated. Then the volumetric behavior up to high pressures (25 MPa) and atmospheric pressure viscosity were experimentally determined. It has been found that the influence of particle size in density is subtle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(88 citation statements)
references
References 25 publications
1
84
0
3
Order By: Relevance
“…The dispersion was performed using an ultrasonic probe (UP400s from Hielscher Company) that has been checked to be the most effective dispersion system (Pastoriza-Gallego et al, 2009;Petzold et al, 2009). Initially, the mixture of nanoparticles with the water was submitted to a sonication treatment for a period of time.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%
“…The dispersion was performed using an ultrasonic probe (UP400s from Hielscher Company) that has been checked to be the most effective dispersion system (Pastoriza-Gallego et al, 2009;Petzold et al, 2009). Initially, the mixture of nanoparticles with the water was submitted to a sonication treatment for a period of time.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%
“…Therefore, the use of carbon nanotubes is limited by its high viscosity. Hence, the combined study of thermal properties (thermal conductivity and specific heat) and rheological properties (viscosity) is of great importance, although only few works include rheological measurements of nanofluids (Lee et al, 2008;Pastoriza-Gallego et al, 2009Yu et al, 2012). As it was done for thermal conductivity, a benchmark study was carried out (Venerus et al, 2010), in order to compare the values of viscosity obtained by different researchers, when the same samples of Al 2 O 3 , SiO 2 , and Mn-Zn ferrite nanofluids were analyzed by several laboratories, at room temperature (ranging from 20 to 26°C).…”
Section: Introductionmentioning
confidence: 99%
“…Both the processing time and the energy influence the dispersion effect. It has been demonstrated that the ultrasonic probe is the most effective dispersion system due to its higher energy density that breaks the agglomerates more easily than the other mechanisms [11,14,15]. Only 2-4 minutes (depending on the conditions of the nanofluid) are needed to obtain well-dispersed suspensions.…”
Section: Introductionmentioning
confidence: 99%